Association of Smoking Cessation and Intentions to Quit: Role of Occupational Status, Health Professional’s Support, and Perceived Risk (Epidemiology, Biostatistics, and Public Health, 2022)
Objectives: Cigarette smoking continues to be the leading cause of preventable morbidity and mortality in the United States. Tobacco related mortality has promoted a massive effort to understand and enhance smoking cessation efforts. In this study, we examine the role of different factors on intentions to quit smoking.Methods: Data is taken from Health Information National Trends Survey (HINTS) 2012. A total of 1745 national representative samples of U.S adults, meeting our research conditions, were included in this study.Results: Multivariate statistical analysis methods were used which showed that employed participants were 6 times more likely to have intentions to quit than participants with other occupational statuses were.  Participants who received support sometimes from health professionals were 9 times more likely to have intention to quit smoking as compared to those who never received support from health professionals.  In addition, race (Hispanic), and age group (35-39 years) are significantly associated with intentions to quit smoking. Perceived personal risk of cancer, perceived compared risk of cancer, and family history of cancer were not significantly associated with intentions to quit smoking.Conclusion: Our study suggests that age, race, occupational status, and help from health professionals are viable intervention targets for smoking cessation interventions. As a key role can be played by health professionals in smoking cessation interventions, future work should evaluate the extent to which health professionals can play a role in smoking cessation intervention.  Smokers should be encouraged to maintain smoke free environments in their homes and offices, by health care providers leading to the protection of non-smokers, lesser convenience for smoking, decreased cigarette consumption, and smoking cues over time.